Compression Mechanical Behaviour of 7075 Aluminium Matrix Composite Reinforced with Nano-sized SiC Particles in Semisolid State. Issue 11 (November 2016) - Jiang, Jufu; Chen, Gang; Wang, Ying
Abstract : The 7075 aluminium matrix composite reinforced with nano-sized SiC particles was fabricated by ultrasonic assisted semisolid stirring method. The compression mechanical behaviour of the fabricated composite in semisolid state was investigated. The results show that the microstructure of the composite before semisolid compression consists of fine and spheroidal solid grains surrounded by liquid phase. Semisolid compression led to a nonuniform plastic deformation of solid grains. A slight plastic deformation occurred in the locations near the free surface due to the dependence of deformation on liquid flow and flow of liquid incorporating solid grains. However, obvious plastic deformation occurred in the central location and location contacting to die due to the contribution of plastic deformation of solid grains. The true stress–strain curve of the sample compressed at 500 °C consists of rapid increase of true stress and steady stage. However, rapid increase of true stress and decrease of true stress and steady stage are involved in the true stress–strain curves of the samples compressed at 550, 560, 570, 580 and 590 °C. The true stress–strain curve at 600 °C is similar to that at 500 °C. Apparent viscosity decreases with an increase of shear rate, indicating a shear thinning occurrence. When soaking time increases from 5 min to 15 min, the peak stress and steady stress decrease significantly. A further increase of the soaking time led to a slight change. Peak stress and steady stress increase with increasing volume fraction of SiC particles. A sudden increase or decrease of compression velocity led to a significant increase or decrease of the steady stress. The destruction of the samples compressed at solid state temperature mainly depends on cracks parallel to compression direction. However, the destruction forms of the samples compressed at semisolid temperatures consist of cracks parallel to compression direction and partial collapse. Increasing soaking time led to an obvious change of the destruction forms. Compression velocity affects slightly the macro appearance of the sample compressed at semisolid temperatures.